Application of three novel ratio difference spectrophotometric methods for the simultaneous estimation of zaltoprofen and paracetamol in combined dosage form - N.K.ZAHIRA; P.N.PRESANNAKUMARAN (International Journal of Pharma and Bio Sciences, 2018)
Ratio difference spectrophotometric method, a novel technique for the determination of binary mixture was developed and validated for the simultaneous estimation of Zaltoprofen (ZLT) and Paracetamol (PAR). The results were compared statistically. Ratio Difference Spectrophotometric Method (RDSM), Mean centering of ratio spectra spectrophotometric method (MCR), Extended Ratio Subtraction Method (EX RSM) are the three novel ideas that can be used to manipulate the data from UV Spectra of mixture without prior separation. The suggested methods were validated in compliance with the ICH guidelines and were successfully applied for determination of ZLT and PAR in their laboratory prepared mixture and commercial Tablet. This is a simple manipulation with maximum reproducibility and robustness, which can be used for the analysis of binary mixture with overlapped spectra for routine QC testing.